Productos Naturales con actividad antimicótica (2004)
ABSTRACT: In the past few decades, a worldwide increase in the incidence of fungal infections has been observed and the resistance of some species of fungus to different fungicidals used in medical practice has also risen. This has led to the search for new antimycotics, particularly those obtained from natural sources such as plants, insects, and land and marine microorganisms. In these natural sources, a series of molecules with antifungal activity against different species of fungus of great clinical importance for humans has been found, and these substances have become an alternative for the development and formulation of new antifungals with fewer side effects, a greater spectrum of action and lower cost than those in current use. In this article, we review the main sources of molecules with antimycotic activity obtained from natural sources.